Carolyn A. Nadeau: Food Matters: Alonso Quijano’s Diet and the Discourse of Food in Early Modern Spain & Monika Linton: Brindisa: The True Food of Spain - Hayward, Vicky (Petits Propos Culinaires, 2017)
Carolyn A. Nadeau: Food Matters: Alonso Quijano’s Diet and the Discourse of Food in Early Modern Spain: University of Toronto Press, 2016: 336 pp., hardback, 65.00. Monika Linton: Brindisa: The True Food of Spain: Fourth Estate, 2016: 544 pp., hardback, £29.95.